A public health and budget impact analysis of vaccinating at-risk adults and the elderly against pneumococcal diseases in Germany. (October 2012) - Jiang, Yiling; Gauthier, Aline; Annemans, Lieven; van der Linden, Mark; Nicolas-Spony, Laurence; Bresse, Xavier
To assess the comparative public health and budget impact over 5 years of several pneumococcal vaccination strategies (23-valent pneumococcal polysaccharide vaccine [PPV23] and/or 13-valent pneumococcal conjugate vaccine [PCV13]) in Germany, within the context of changing invasive pneumococcal disease (IPD) incidence over time. A multi-cohort, population-based Markov model was developed. Uncertainty around vaccine effectiveness, costs and IPD incidence change was handled through scenario analyses. Between 2012 and 2016, the introduction of PCV13 in adults, compared with the use of PPV23, would be associated with a net estimated budget increase of €59.7 million (+6.7%) to €151.6 million (+13.7%). Impact on IPD incidence ranged from -113 cases (-0.8%) to +298 cases (+2.8%). Introducing PCV13 in adults is expected to significantly affect healthcare budgets. Adult vaccination with PPV23 remains the optimal vaccination strategy from public health and budget perspectives.